Peroxisomes and Oxidative Stress: Their Implications in the Modulation of Cellular Immunity During Mycobacterial Infection - Ganguli, Geetanjali; Mukherjee, Utsav; Sonawane, Avinash (Frontiers in Microbiology, 2019)
Host redox dependent physiological responses play crucial roles in the determination of mycobacterial infection process. Mtb explore oxygen rich lung microenvironment to initiate infection process, however, later on the bacilli adapt to oxygen depleted conditions and become non-replicative and unresponsive towards anti-TB drugs to enter in the latency stage. Mtb is equipped with various sensory mechanisms and a battery of pro- and anti-oxidant enzymes to protect themselves from the host oxidative stress mechanisms. After host cell invasion, mycobacteria induce the expression of NADPH oxidase 2 (NOX2) to generate superoxide radicals (O2-), which are then converted to more toxic hydrogen peroxide (H2O2) by superoxide dismutase (SOD) and subsequently reduced to water by catalase. However, the metabolic cascades and their key regulators associated with cellular redox homeostasis are poorly understood. Phagocytosed mycobacteria en route through different subcellular organelles, where the local environment generated during infection determines the outcome of disease. For a long time, mitochondria were considered as the key player in the redox regulation, however, accumulating evidences reported vital role for peroxisomes in the maintenance of cellular redox equilibrium in eukaryotic cells. Deletion of peroxisome-associated peroxin genes impaired detoxification of reactive oxygen species (ROS) and peroxisome turnover post infection, thereby leading to altered synthesis of transcription factors, various cell-signaling cascades in favor of the bacilli. This review focuses on how mycobacteria would utilize host peroxisomes to alter redox balance and metabolic regulatory mechanisms to support infection process. Finally, we attempted to highlight implications of peroxisome biogenesis in the modulation of host immune responses in the perspectives of enhancing cellular immunity to clear mycobacterial infection.